Accuracy of Measles Immunization Records and Reporting in Maternal and Child Health Card and Cohort Book - Finazis, Rekha (Jurnal Berkala Epidemiologi, 2014)
ABSTRACTInfectious diseases such as diseases that can be prevented by immunization remains a problem in Indonesia, one of which is measles. The government has sought to prevent through measles immunization in infants aged 9 months. Seeing the efforts that have been made through measles immunization program and still finding measles in the community, it is necessary to evaluate the success of programs related to the measles immunization. This study was conducted to determine the problems that occur in terms of recording and reporting of data related to measles immunization in particular measles immunization data quality. The population was 5 posyandu with the highest number of children under five in the region of new health centers Gunung Anyar city of Surabaya. The number of respondents is as much as 50 respondents with details of each neighborhood health center will take 10 respondents. The sample selection is done through a rapid survey method. The variables studied were the quality of immunization data on books maternal and child health card or other health records compared with immunization data on a cohort book. Other variables are the quality of data on infants in posyandu regiter book by book cohort. The results showed that the percentage of the suitability of the data of measles in the community with book five cohort remains low in the neighborhood health center. Meanwhile, the percentage of suitability daata on the register books with babies in posyandu cohort book is also fairly low. This suggests that the quality of data recorded measles immunization is relatively low.Keywords: immunization, measles,infant recording, reporting